2022
DOI: 10.1063/5.0087055
|View full text |Cite
|
Sign up to set email alerts
|

Large-eddy simulations of self-excited thermoacoustic instability in a premixed swirling combustor with an outlet nozzle

Abstract: Reducing the footprint of greenhouse gases and nitrogen oxides (NOx) emissions from combustion systems means that they have been operating under lean or ultra-lean fuel–air premixed conditions. Under such conditions, self-excited large-amplitude pulsating thermoacoustic instabilities may occur, characterized by deafening combustion noises and even “violent” structural vibrations, which is, therefore, highly undesirable in practice. By conducting chemical reaction-thermodynamics-acoustics-swirling flow coupling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…LES was applied to a realistic gas turbine combustion chamber configuration to investigate the evaluation of the terms in the acoustic energy equation and the identification of the mechanism driving the oscillation. 8 Sun et al 9 used the LES method to explore the generation and mitigation mechanisms of self-excited pulsation oscillations in a methane-fueled swirl combustor with and without an exit nozzle. To overcome the high computational cost required for LES, non-stationary Reynolds-averaged Navier-Stokes (URANS) simulations are used to obtain results as close to LES as possible.…”
Section: Introductionmentioning
confidence: 99%
“…LES was applied to a realistic gas turbine combustion chamber configuration to investigate the evaluation of the terms in the acoustic energy equation and the identification of the mechanism driving the oscillation. 8 Sun et al 9 used the LES method to explore the generation and mitigation mechanisms of self-excited pulsation oscillations in a methane-fueled swirl combustor with and without an exit nozzle. To overcome the high computational cost required for LES, non-stationary Reynolds-averaged Navier-Stokes (URANS) simulations are used to obtain results as close to LES as possible.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of combustion instability, pressure fluctuation has negative impacts on the combustion system (Huang and Yang 2009). Combustion instability is a complex physicochemical process in which fluid, acoustics and combustion are coupled, and it is usually studied by experiment (Harvazinski et al 2015) and numerical simulation (Zhao et al 2019;Sun et al 2022). As for the mechanisms of combustion instability, the excitations have not yet been fully understood (Murayama and Gotoda 2019).…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Acoustic damping performances of Helmholtz resonators could be evaluated by conducting time-or frequency-domain simulations. [5][6][7]12 The governing equations are coupled nonlinear Navier-Stokes equations. The vorticity-involved damping physics of Helmholtz resonators are visualized by these simulations 12,13,15 or flow visualizations or laserinvolved experimental measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Optimizing the resonator neck may increase or decrease the transmission losses by 5–15 dB over a wide frequency range. Wu et al 5 numerically investigated aeroacoustics damping performance of a Helmholtz resonator in the presence of a joint bias-grazing flow. They showed that when a joint bias-grazing flow is present, the effects of the cooling/bias flow may give rise to a transmission loss peak being reduced around 5 dB.…”
Section: Introductionmentioning
confidence: 99%